Cover Feature: A Metal‐Free Electrode: From Biomass‐Derived Carbon to Hydrogen (ChemSusChem 16/2020). Issue 16 (6th August 2020) - Ding, Yuxiao; Greiner, Mark; Schlögl, Robert; Heumann, Saskia
Abstract : The Cover Feature shows that biomass‐derived carbons can be applied as sacrificial electrodes to produce hydrogen. This sustainable solution offers a real option for future energy systems. More information about the technical and chemical feasibilities can be found in the Full Paper by Y. Ding et al .